Kinetics of Oxidation of Glutathione by Micelle Trapped Tris(benzhydroxamato)iron(III) - B. L. Hiran; S. S. Dulawat; Renu Rathore; Neeru Rathore (E-Journal of Chemistry)
Kinetics of the oxidation of glutathione (GSH) by micelle Sodium dodecyl sulphate (SDS) trapped tris(benzhydroxamato)iron(III) (TBH) at pH 3.3 and at 298 K has been described. The reaction is first order in TBS and GSH. Increase in pH decreased the rate. Order in H+ is one The reaction between TBH and GSH on micellar surface (Stern layer) differs from that occurring in bulk aqueous phase in absence of micelle (SDS). Reactive FeL3 species on micellar surface is FeL2+.